Strategi dan Metode Perbaikan Kerusakan Beton Pada PLTU X - Prima Ranna; Iwan B Santoso; Jason Lim (Jurnal Infrastruktur, 2025)
The use of large volumes of concrete often results in damage such as honeycombs and cracks, which can threaten the strength and durability of the structure. One method of repairing such damage is through demolition. However, demolishing concrete structures due to defects can be costly. Technology advancements have led to the development of repair methods that do not require dismantling the structure. This can be done with Root Cause Analysis (RCA) to identify the factors causing the damage, as well as Forensic Assessment using Ultrasonic Pulse Velocity (UPV) and Ultrasonic Pulse Echo (UPE) to assess the condition of the concrete. The analysis showed that there were several main factors that caused the damage, including the use of inappropriate vibrators and a lack of worker skills. This research demonstrates that not all damage requires total demolition; there are various repair methods that can extend the lifespan of the structure without incurring high costs. This research provides a step for construction management in aligning repair strategies to improve the durability and safety of concrete structures in power plants.